Diagnosis of advanced cervical cancer, missed opportunities? - Jérémie Mattern; Irène Letendre; Jeanne Sibiude; Cécile Pénager; Asma Jnifen; Fatoumata Souare; Sophie Ayel; Thuy Nguyen; Laurent Mandelbrot (BMC Women's Health, 2022)
Abstract Background Cervical cancer is common worldwide. Despite the existence of primary and secondary prevention strategies, the survival rate is decreasing in France due to an increasing proportion of advanced-stage cancer. Our objective was to determine the factors associated with a diagnosis of cervical cancer at advanced stages in an urban population in France. Methods A retrospective study was conducted on all consecutive records of patients diagnosed with cervical cancer between January 2006 and December 2018 in a single center in Paris. The data collected were demographic characteristics, medical and gynecological history, circumstances of diagnosis, diagnostic and therapeutic management. The patients were divided into two groups according to the FIGO 2018 stage at diagnosis: group A stages IA1 to IB2 and group B advanced stages IB3 to IVB. Results Among 96 patients who were diagnosed with cervical cancer, 25 (26%) were in group A and 71 (74%) in group B. Women in group B had less frequently received regular gynecological care than in group A (36% vs 84.2%, p < 0.001) and fewer had Pap test screening in the previous 3 years (30.4% vs 95.0%, p < 0.001). Parity greater than 3 was more frequent in group B (69.6% vs 42.9%, p = 0.031). The diagnosis was made during a routine examination or cervical smear in only 9.23% and 16.18% respectively in group B, versus 60% of cases in 45.82% of cases in group A (p < 0.001 and p = 0.003). Vaginal bleeding was observed in 85.29% in group B versus 36% in group A (p < 0.001). Histological type was squamous cell carcinoma 87.32% of group B and 56% of group A (p < 0.001). Conclusion Diagnosis of cervical cancers at advanced stages occurred mostly in women who did not benefit from the recommended screening. Universal access to screening is necessary for the prevention and early treatment of cervical cancer.